Analisis Investasi Dan Kelayakan Usaha Pada PT. Warmare Jaya Mandiri (WJM) Manokwari Selatan - Rosita Rosita; Yulius Heri Saptomo (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
A business feasibility study is an assessment of whether or not the business being implemented is feasible. It is feasible because it provides benefits for the company that runs it, for investors, creditors, the government and society. The purpose of this research is to analyze the feasibility of the company's business in carrying out stone and sand mining carried out by PT. Warmare Jaya Mandiri. In this research, the data used is financial data on capital, production, selling prices, salary costs for managers, administration, equipment operators, drivers and daily labor. The analysis techniques used to process this data are Net Present Value, Net Benefit Cost Ratio, Internal Rate of Return and Pay Back Period. From the results of the Net Present Value analysis, a value of IDR 2,289,154,040 was obtained. The results were positive and declared feasible. Furthermore, for the Benefit Cost Ratio, the B/C calculation result is 2.43 > 1, so the investment is declared suitable to continue. The next method is the IRR method to obtain a value of 26.80%, this value is above the required minimum interest value. From the pay back period analysis, the pay back period analysis is estimated to be able to return all investment costs after 4 years and 2 months.